Further Characterization of the Capsule-Like Complex (CLC) Produced by Francisella tularensis Subspecies tularensis: Protective Efficacy and Similarity to Outer Membrane Vesicles - Champion, Anna E.; Bandara, Aloka B.; Mohapatra, Nrusingh; Fulton, Kelly M.; Twine, Susan M.; Inzana, Thomas J. (Frontiers in Cellular and Infection Microbiology, 2018)
Francisella tularensis is the etiologic agent of tularemia, and subspecies tularensis (type A) is the most virulent subspecies. The live vaccine strain (LVS) of subspecies holarctica produces a capsule-like complex (CLC) that consists of a large variety of glycoproteins. Expression of the CLC is greatly enhanced when the bacteria are subcultured in and grown on chemically defined medium. Deletion of two genes responsible for CLC glycosylation in LVS results in an attenuated mutant that is protective against respiratory tularemia in a mouse model. We sought to further characterize the CLC composition and to determine if a type A CLC glycosylation mutant would be attenuated in mice. The CLCs isolated from LVS extracted with 0.5% phenol or 1 M urea were similar, as determined by gel electrophoresis and Western blotting, but the CLC extracted with urea was more water-soluble. The CLC extracted with either 0.5% phenol or 1 M urea from type A strains was also similar to the CLC of LVS in antigenic properties, electrophoretic profile, and by transmission electron microscopy (TEM). The solubility of the CLC could be further enhanced by fractionation with Triton X-114 followed by N-Lauroylsarcosine detergents; the largest (>250 kDa) molecular size component appeared to be an aggregate of smaller components. Outer membrane vesicles/tubules (OMV/T) isolated by differential centrifugation and micro-filtration appeared similar to the CLC by TEM, and many of the proteins present in the OMV/T were also identified in soluble and insoluble fractions of the CLC. Further investigation is warranted to assess the relationship between OMV/T and the CLC. The CLC conjugated to keyhole limpet hemocyanin or flagellin was highly protective against high-dose LVS intradermal challenge and partially protective against intranasal challenge. A protective response was associated with a significant rise in cytokines IL-12, IL-10, and IFN-γ. However, a type A CLC glycosylation mutant remained virulent in BALB/c mice, and immunization with the CLC did not protect mice against high dose respiratory challenge with type A strain SCHU S4.